La crisis de los años 1785-1786 en Michoacán: ¿El 'Gran Hambre' o las grandes epidemias? (Tzintzun, Revista de Estudios Históricos, 2016)
he 1785-1786 crisis is considered as a food crisis. he loss of harvest caused a highdeath toll in New Spain, due to famine and the weakness of the population exposedto various illnesses. Among the main initiatives in Michoacán were those of BishopObispo Fray Antonio de San Miguel and Dean José Pérez Calama, aiming at avoidingserious social problems which entailed the lack of food and its high price. he measurestaken by the town council and the counsil of canons were successful in avoiding thescarcity and shortage in corn, however, a lot of people died in this period, especially in1786. he high death toll can be explained by the epidemics which started to spread inVirreinato. here are testimonies and research papers on the high number of humanlives taken by the plague, whereby the general reason for death was high fever. hesecrises had diferent impacts on the various towns that this study focuses on: Valladolid,Pátzcuaro y Uruapan, partly due to the quality of parish registers, but also becausethe various illnesses were treated diferently among diferent age groups. heir impactcan be measured by Lorenzo del Panta and Massimo Livi-Bacci’s formula, applied indeath registers. he crises brought by the arrival of migrants from El Bajío, who probablybrought with them the epidemics that spread in Michoacán.
Keywords: death crisis; Lorenzo del Panta and Massimo Livi-Bacci’s formula; epidemics; “Big Hunger”; Michoacán